A clinical analysis of sinonasal squamous cell carcinoma: a comparison of de novo squamous cell carcinoma and squamous cell carcinoma arising from inverted papilloma. (31st July 2020) - Yasumatsu, Ryuji; Jiromaru, Rina; Hongo, Takahiro; Uchi, Ryutaro; Wakasaki, Takahiro; Matsuo, Mioko; Taura, Masahiko; Nakagawa, Takashi
Abstract: Background: Sinonasal squamous cell carcinoma (SCC) is a rare tumor arising either de novo or in association with inverted papillomas (IPs). Objectives: The aim of this study was to investigate and compare the oncological features and prognosis of patients with sinonasal SCCs based on their etiology. Material and methods: The medical records of 117 patients who had been diagnosed with de novo SCC or those arising from IP (IP-SCC) were retrospectively reviewed. In situ hybridization analyses to detect HPV 16/18DNA and p16 immunohistochemistry were also performed in 10 cases with IP-SCC. Results: The three-year disease-specific survival (DSS) rate was higher in cases with T1, 2 and 3 than in cases with T4 in both tumor groups. T4 cases with de novo SCC had a better DSS than those with IP-SCCs. HPV16/18 was not detected in any of the 10 IP-SCCs. Conclusions and significance: T4 cases with de novo SCC tended to have a better DSS than those with IP-SCC. Since some T4 patients with IP-SCC were found to have a highly aggressive disease, careful treatment planning should be performed. High-risk HPV may not play a vital role in the carcinomatous transformation of most IP-SCC cases.